C-Terminal Amination of a Cationic Anti-Inflammatory Peptide Improves Bioavailability and Inhibitory Activity Against LPS-Induced Inflammation - Zhang, Lulu; Wei, Xubiao; Zhang, Rijun; Koci, Matthew; Si, Dayong; Ahmad, Baseer; Guo, Henan; Hou, Yanfei (Frontiers in Immunology, 2021)
Lipopolysaccharide (LPS) has been implicated as a major cause of inflammation and an uncontrolled LPS response increases the risk of localized inflammation and sepsis. While some native peptides are helpful in the treatment of LPS-induced inflammation, the use of these peptides is limited due to their potential cytotoxicity and poor anti-inflammatory activity. Hybridization is an effective approach for overcoming this problem. In this study, a novel hybrid anti-inflammatory peptide that combines the active center of Cathelicidin 2 (CATH2) with thymopentin (TP5) was designed [CTP, CATH2 (1-13)-TP5]. CTP was found to have higher anti-inflammatory effects than its parental peptides through directly LPS neutralization. However, CTP scarcely inhibited the attachment of LPS to cell membranes or suppressed an established LPS-induced inflammation due to poor cellular uptake. The C-terminal amine modification of CTP (CTP-NH2) was then designed based on the hypothesis that C-terminal amidation can enhance the cell uptake by increasing the hydrophobicity of the peptide. Compared with CTP, CTP-NH2 showed enhanced anti-inflammatory activity and lower cytotoxicity. CTP-NH2 not only has strong LPS neutralizing activity, but also can significantly inhibit the LPS attachment and the intracellular inflammatory response. The intracellular anti-inflammatory effect of CTP-NH2 was associated with blocking of LPS binding to the Toll-like receptor 4-myeloid differentiation factor 2 complex and inhibiting the nuclear factor-kappa B pathway. In addition, the anti-inflammatory effect of CTP-NH2 was confirmed using a murine LPS-induced sepsis model. Collectively, these findings suggest that CTP-NH2 could be developed into a novel anti-inflammatory drug. This successful modification provides a design strategy to improve the cellular uptake and anti-inflammatory activity of peptide agents.